Optimizing supercritical antisolvent process parameters to minimize the particle size of paracetamol nanoencapsulated in L-polylactide - Kalani, Mahshid; Yunus, Robiah; Abdullah, Norhafizah (Dove Medical Press, 2011)
Background: The aim of this study was to optimize the different process parameters including pressure, temperature, and polymer concentration, to produce fine small spherical particles with a narrow particle size distribution using a supercritical antisolvent method for drug encapsulation. The interaction between different process parameters was also investigated. Methods and results: The optimized process parameters resulted in production of nanoencapsulated paracetamol in L-polylactide with a mean diameter of approximately 300 nm at 120 bar, 30°C, and a polymer concentration of 16 ppm. Thermogravimetric analysis illustrated the thermal characteristics of the nanoparticles. The high electrical charge on the surface of the nanoparticles caused the particles to repel each other, with the high negative zeta potential preventing flocculation. Conclusion: Our results illustrate the effect of different process parameters on particle size and morphology, and validate results obtained via RSM statistical software. Furthermore, the in vitro drug-release profile is consistent with a Korsmeyer–Peppas kinetic model.